Youth magazines from the millennial generation to the Alpha generation: analysis of the evolution in the consumption habits of Spanish teenage girls - Fernández-Castrillo , Carolina; González-González, Adriana (Estudios sobre el Mensaje Periodístico, 2025)
The research addresses the evolution of the consumption habits of teenage Spanish girls’ magazines addressed to the millennial, centennial, and Alfa generations. For this study, adolescence is considered to begin at age 12. The article analyzes what happened during adolescence over a 30-year period, from 1993 to 2023. The paper sets out three main objectives from a gender perspective: the evaluation of the media landscape at each time in order to detect the boom and crisis periods of youth magazines in Spain; the identification of the main themes addressed in each period related to the construction of feminine identity; and, finally, the proposal of an information consumption categorization established from generational patterns, paying special attention to the growing prominence of new information channels in connective environments in generation Z and Alpha. The results confirm the currentlly crisis of youth magazines and shed light on new consumption patterns. While millennial teens' focus was on relationships with boys, this topic has diminished among Generation Alpha. Instead, external perception and the pressure to conform to normative beauty standards remain central.
Keywords: generation Z; gender identity; consumption pattern; early adolescence; teenage girls’ magazine; information trend